2010 International Conference on Science and Social Research (CSSR 2010) 2010
DOI: 10.1109/cssr.2010.5773853
|View full text |Cite
|
Sign up to set email alerts
|

Fraud diamond risk indicator: An assessment of its importance and usage

Abstract: Recent fraud surveys published by large accounting professional firms in Malaysia (e.g. KPMG 2009, PriceWaterHouseCooper 2009) indicated that preceding actual financial fraud cases, red flags or indicators have always been detected by auditors. Nevertheless such red flags are often ignored or "pushed under the carpet" by companies who are victims of such frauds. The reasons for ignoring the indicators vary from "an effort towards facesaving" to "the amount is too small to affect the company's performance". Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 3 publications
4
38
0
5
Order By: Relevance
“…While [11] find that "opportunity red flags" is the top five important indicator for internal and government auditors. Opportunity being look as an influences to the distribution of criminal behavior, for example if the employee have the financial pressure but thus not have the opportunity then the fraud could not be happens probably high.…”
Section: Fraud Trianglementioning
confidence: 92%
See 3 more Smart Citations
“…While [11] find that "opportunity red flags" is the top five important indicator for internal and government auditors. Opportunity being look as an influences to the distribution of criminal behavior, for example if the employee have the financial pressure but thus not have the opportunity then the fraud could not be happens probably high.…”
Section: Fraud Trianglementioning
confidence: 92%
“…To assess the fraud risk, auditor need to understand the opportunity in the fraud triangle because opportunity allow fraudster to seek a solution through illegitimate means [8]. Plus the previous research [5], [11] also suggesting the opportunity is the important element when assessing the fraud risk.…”
Section: Fraud Trianglementioning
confidence: 99%
See 2 more Smart Citations
“…In the past, much opportunity is possible for employees to commit white collar crimes if internal control of the management is low (Kassem & Higson, 2012;Wolfe & Hermanson, 2004). Previous studies (Dinapoli, 2008;Omar & Din, 2010;Lou &Wang, 2011, andDellaportas, 2013) have indicated that various elements, such as unclear separation of roles and responsibilities, poor documentation on policies, procedures and guidelines, insufficient physical controls by security guards, entering the transaction in an untimely manner, unrestricted access to corporate check books, and insecure control of cash boxes, present numerous opportunities for fraud to occur within the banking sector. Thus, management should emphasize on policy implementation and strengthen the power of internal control.…”
Section: Discussionmentioning
confidence: 99%